(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Evaluated effects of the treatment with imatinib of chronic myeloid leukemia patients with additional cytogenetic abnormalities (ACAs) since 2012 to March 2025. Subjects: Patients were diagnosed chronic myeloid leukemia (CML) in chonic phase with additional cytogenetic abnormalities and were treated with imatinib in Hematology and Blood transfution center Bachmai Hospital from 2012 to 3/2025. Method: Retrospective cohort study. Results: At the 35 patients CML with ACAs were treated with imatinib, the most common additional cytogenetic abnormalities include additional Ph translocation (34,2%), complex karyotype (28,6%), trisomy 8 (11,4%) and second Ph (11,4%). Rate of complete hematologic response after 3 months was 91,4%. Rate of complete cytogenetic response after 12 months was 42,9%. Rate of major molecular response was 48,6%. The survival rate was 51,4%. The overall 5-years relative survival rate was 47,1%. Conclusion: The patients with ACAs were treated with imatinib had rate of complete hematologic response after 3 months was 91,4%, rate of complete cytogenetic response after 12 months was 42,9%, rate of major molecular response was 48,6%, the overall 5-years relative survival rate was 47,1%.